Trachoma in the Gambia. Issue 8 (1st August 1998) - Dolin, P J; Faal, H; Johnson, G J; Ajewole, J; Mohamed, A A; Lee, Pak S
Abstract : BACKGROUND: As part of the second National Survey of Blindness and Low Vision in the Gambia carried out in 1996, all survey participants were examined for signs of trachoma. The findings were compared with the results of the first survey in 1986, which used the same sampling strategy. METHODS: A multistage stratified cluster random sample, with proportional probability sampling, was obtained. Stratification included settlement size (less than 400 residents, and 400 and more residents). All subjects were examined for trachoma using the simplified WHO grading system. RESULTS: Of the sample of 14 110 people, 13 047 (92.5%) were examined. Active inflammatory trachoma (grade TF or TI) was found in 3.0% of all age groups and 5.9% of children aged 0–9 years old. Trichiasis was found in 3.3% and trachomatous corneal opacities in 0.9% of adults aged 30 and over. The prevalence of blinding trachomatous corneal opacities was 0.02%, compared with 0.10% 10 years previously. CONCLUSION: Compared with a previous national survey undertaken in 1986, prevalence of active trachoma has fallen by 54%. There has been an 80% relative reduction in blinding trachomatous corneal opacities over the 10 year period.